Pengaruh Kualitas Produk, Harga dan Citra Merek Terhadap Keputusan Pembelian Pembersih Toner VIVA Kosmetik Lokal di Sidoarjo - Lianawati; Rizky Eka Febriansah; Dewi Komala Sari (Journal of Business Economics and Agribusiness, 2026)
The competition in the cosmetics industry has made local cosmetics pr saveral companies required to maintain their business by implementing the right marketing strategies to keep up with developments. The research aims to analyze the influence of product quality, price and barnd image on the puchasing decisions of cleansear toner viva cosmetics in Sidoarjo area. The type of research used is quantitative method with the population being the community in Sidoarjo. This research sampling technique uses non-probability sampling with puposive sampling method and total of 100 respondents. The data collection technique is carried out throught the distribution of questionnaires measured using a Likert scale. The data analysis technique of this research uses multiple linear analysis with the help of SmartPls 3 software. The research findings indicate that quality product affects positive and significant to purchasing decision, that price affects positive and no significant, that brand image affects purchasing decision in Sidoarjo.